2019
DOI: 10.1007/s11199-019-1006-0
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Associations and Conscious Attitudes Predict Different Aspects of Men’s Intimate Partner Violence and Sexual Harassment Proclivities

Abstract: Intimate partner violence against women (IPV) and sexual harassment are both widespread.Research on their causes and attitudinal correlates has rarely examined implicit, automatic cognitive associations related to the partner (in IPV aggressors) or to women (in sexual harassment offenders). The aim of the present research was to study these implicit associations in 129 male German students. Participants completed scales of hostile sexism (HS), masculine gender role stress (MGRS), short-term (STMO) and long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Studies that have examined the proclivity toward domestic violence mostly used self-report questionnaires or scenarios to assess, within intimate relationships, the frequency of aggressive behavior (e.g., cyberbullying of girlfriends; Martinez-Pecino & Durán, 2019) or violence (e.g., Renzetti et al, 2018; Zapata-Calvente et al, 2019). HS in men is positively associated with greater perpetration of physical and psychological aggression and violence against women partners (e.g., Juarros-Basterretxea et al, 2019; Whitaker, 2013; Zapata-Calvente et al, 2019), and may also generalize to aggressive parenting (Overall et al, 2021). A cross-cultural study that used national statistics for assaults and homicides lends weight to this evidence by showing that national levels of HS (with values derived from Glick et al, 2004) were associated with women’s victimization rates (Archer, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have examined the proclivity toward domestic violence mostly used self-report questionnaires or scenarios to assess, within intimate relationships, the frequency of aggressive behavior (e.g., cyberbullying of girlfriends; Martinez-Pecino & Durán, 2019) or violence (e.g., Renzetti et al, 2018; Zapata-Calvente et al, 2019). HS in men is positively associated with greater perpetration of physical and psychological aggression and violence against women partners (e.g., Juarros-Basterretxea et al, 2019; Whitaker, 2013; Zapata-Calvente et al, 2019), and may also generalize to aggressive parenting (Overall et al, 2021). A cross-cultural study that used national statistics for assaults and homicides lends weight to this evidence by showing that national levels of HS (with values derived from Glick et al, 2004) were associated with women’s victimization rates (Archer, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Articles on domestic violence varied in terms of the stage of the intimate relationship that was examined, ranging from dating (e.g., Sánchez-Hernández et al, 2020) to committed relationships (e.g., Zapata-Calvente et al, 2019) and marriage (e.g., Overall et al, 2021). 9 Studies that have examined the proclivity toward domestic violence mostly used self-report questionnaires or scenarios to assess, within intimate relationships, the frequency of aggressive behavior (e.g., cyberbullying of girlfriends; Martinez-Pecino & Durán, 2019) or violence (e.g., Renzetti et al, 2018;Zapata-Calvente et al, 2019). HS in men is positively associated with greater perpetration of physical and psychological aggression and violence against women partners (e.g., Juarros-Basterretxea et al, 2019;Whitaker, 2013;Zapata-Calvente et al, 2019), and may also generalize to aggressive parenting (Overall et al, 2021).…”
Section: Domestic Violence (N Articles = 66)mentioning
confidence: 99%
“…In the workplace, SH is still generally perceived as behavior directed at women by men (McCabe & Hardam 2005). SH can be verbal, nonverbal, or physical behaviors (Crowley et al, 2019) that are unwelcome and observed negatively by the target (Zapata-Calvente et al, 2019). SH behaviors are such as unwanted sexual comments or jokes; unwelcome touches in a sexual way; and undesirable sexual rumors being spread about someone; repeated requests for dates, whistles, staring, and various types https://jaauth.journals.ekb.eg / of unwelcome physical contact of a sexual nature (McCabe & Hardam 2005;Crowley et al, 2019).…”
Section: )mentioning
confidence: 99%
“…The impacts of SH on women employees in the service sector generally and hotels specifically include increased absenteeism, poor customer service, and low profitability (Sims et al, 2005;Kensbock et al, 2015;Morgan & Pritchard 2019;Teo et al, 2020), poor working relationships, low morale (Mkono 2010), low self-esteem, insufficient organizational commitment (Long et al, 2016) negative corporate reputation from the public (Ali et al, 2015). Also, SH has an impact on mental, https://jaauth.journals.ekb.eg / psychological, and physical health as evidenced in their higher levels of symptoms such as loss of confidence, stress, anxiety, lack of security, bad dreams, and difficulty sleeping, a sense of fear, shame, confusion, depression, post-traumatic stress disorder, headaches and gastric problem (Gilbert et al, 1998;Murdoch & McGovern 1998;Gettman et al, 2007;Willness et al, 2007;Ali et al, 2015;Sepulveda 2015;Long et al, 2016;Zapata-Calvente et al, 2019;Jung & Yoon 2019).…”
Section: 2causes and Impacts Of Sexual Harassment In The Hospitality Industrymentioning
confidence: 99%
“…Indirect measures of SDS endorsement such as the Implicit Association Test (IAT; Greenwald et al, 1998), tapping into automatic cognitions, may bear advantages over self-report measures (Zapata-Calvente et al, 2019). The IAT has, in its relatively brief history, become known as a psychometrically sound instrument (Cunningham et al, 2001) that is able to capture individuals' implicit associations between semantic categories (Greenwald et al, 1998).…”
Section: Introductionmentioning
confidence: 99%